Effect of dilution rate, storage time and storage temperature on goat sperm quality - Tran Thi Thanh Khuong; Nguyen Thi Bich Thuy (Vietnam Journal of Science, Technology and Engineering)
Artificial insemination is a technique that facilitates the rapid development of cattle herds, improves breeds, and produces healthy, high-yield livestock. The liquid storage of semen is an effective method for short-term preservation to support artificial insemination. The Mekong Delta offers natural conditions favourable for goat farming. This study aimed to determine the optimal temperature, dilution ratio, and storage duration for preserving goat sperm in Tris-Citrate-Glucose (TCG) medium. The experiment comprised six treatments, each repeated eight times. After collection, semen samples were diluted in TCG medium at ratios of 1:25, 1:250, and 1:2500, and stored at two temperatures: 5°C and 15°C. Sperm quality was evaluated at six specific preservation intervals: 0, 6, 12, 48, and 72 hours. The results indicated that goat sperm quality was best after 72 hours of storage when diluted at a ratio of 1:25 and stored at 15°C. Specifically, after 72 hours of storage at 15°C, samples with a dilution ratio of 1:250 recorded overall motility, progressive motility, viability, and membrane integrity rates of 70.10%, 44.79%, 72.33%, and 48.50%, respectively. In conclusion, the optimal conditions for preserving goat sperm were achieved with a dilution ratio of 1:250 at 15°C for up to 72 hours.